Arctic fjord during warming: Planktonic point of view - J. Wiktor; M. Głuchowska; K. Błachowiak-Samołyk; K. Piwosz; S. Kwaśniewski; K. Jankowska; K. Dmoch; J. M. Węsławski (Ukrainian Antarctic Journal, 2022)
The climate affects aquatic ecosystems worldwide, yet the most dramatic impact has been observed in Polar Regions. The presented study aimed to test the hypothesis that changes in biodiversity are linked to changes in the food web functioning under different temperature conditions, with large species dominant in cold waters and smaller species dominant in warmer waters. Two sites with contrasting hydrology were surveyed in summer 2005 in Hornsund (west Spitsbergen). The first site was located close to the fjord entrance and was strongly influenced by the Atlantic waters (WARM). The second was located deep inside the fjord, where the water is fresher and colder due to glacier meltwater runoff (COLD). Temperature, salinity and photosynthetic active radiation were measured, nutrient concentrations and chlorophyll a were analyzed. Plankton biota, including different fractions of zooplankton, phytoplankton and bacteria was collected and enumerated. The temperature differences were the most pronounced out of the abiotic parameters measured. In particular, the COLD site was characterized by lower water temperature and higher turbidity due to the influence of meltwater. Significant differences in the composition and the quantitative ratios of plankton biota were noted, with the most dramatic variation in the number of microplankton taxa and their biomass. The overall plankton biomass at the WARM site (91 mg C ⋅ m–3) was higher than that at the COLD site (71 mg C ⋅ m–3), as well as the primary production rates. Microplanktonic assemblages at the WARM site included twice as many taxa. The protists constituted more than half of the plankton biomass at the WARM site (53.2%), whereas their share at the COLD site was slightly higher (63.6%). The nanoplankton fraction was numerically dominant among the protists, whereas copepods were the main component of the zooplankton biomass. The differences in planktonic communities’ compositions observed between the two sites might have arisen due to the influence of turbid meltwater runoff, which eliminates larger, strictly autotrophic and decreases primary production.